PENGARUH PRIBADI, SOSIAL DAN BUDAYA TERHADAP KEPUTUSAN MEMILIH PEMBIAYAAN PENSIUN SYARIAH - Muhammad Soberi; Khoirini Lufilia Suyono; Ahmad Saifurriza Effasa (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
This study aims to determine the personal, social, and cultural influences partially and simultaneously on the decision to choose Sharia pension financing. The research sample was 78 respondents, namely pension financing customers of Bank Syariah Mandiri Branch Office Sumberrejo. Data analysis using Multiple Linear Regression Analysis and partial hypothesis testing with the help of SPSS version 22 software. The results show that personal and cultural variables have a significant effect on the decision to choose retirement financing, social variables do not have a significant effect on the decision to choose pension financing, and personal variables have the most dominant influence on the decision to choose Islamic pension financing. The implication of the research result is that it recommends that Bank Syariah Mandiri should maintain and maintain the element of sharia which differentiates it from conventional banks in marketing to retirees. As well as for the Sales Force so as not only to socialize the sharia pension program to employees or employees, but also to entrepreneurs.